2017
DOI: 10.1080/14760584.2017.1335603
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of protection for inactivated enterovirus 71 vaccine: the analysis of immunological surrogate endpoints

Abstract: NCT01508247.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Nonetheless, it is important to evaluate the vaccine in different populations especially in countries where other EV-A71 genotypes are circulating.The neutralization titres were significantly higher in vaccine groups compared with placebo groups, and recipients of all the three vaccines demonstrated high geometric mean titres up to 2 years later.A neutralization titre of >1:16 is suggestive of cross-protection against other genotypes,175 and a titre of >1:42 has been recently been proposed as a correlate of long-term protection 182. However, all three vaccines do not offer cross-protection against other enteroviruses [173][174][175]177,178.…”
mentioning
confidence: 99%
“…Nonetheless, it is important to evaluate the vaccine in different populations especially in countries where other EV-A71 genotypes are circulating.The neutralization titres were significantly higher in vaccine groups compared with placebo groups, and recipients of all the three vaccines demonstrated high geometric mean titres up to 2 years later.A neutralization titre of >1:16 is suggestive of cross-protection against other genotypes,175 and a titre of >1:42 has been recently been proposed as a correlate of long-term protection 182. However, all three vaccines do not offer cross-protection against other enteroviruses [173][174][175]177,178.…”
mentioning
confidence: 99%
“…Zhu and colleagues suggested that long-term protection is afforded when a standardized IU is no less than 70.2IU/ml. [22] Using this criterion, 98.96%, 99.17%, and 99.79% subjects in our study may have long-term protection from EV-A71 related diseases, regardless of which vaccine is used.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies showed that the C-EV71 vaccine had conveyed good immunogenicity in children aged 36-71 months in phase III and IV clinical trials. 24,25 Additionally, the B-EV71 vaccine in children aged 36-71 months was also non-inferior to that in children aged 6-35 months. The anti-EV71 neutralising antibody of children aged 6-35 months in this study was similar to that reported in the lot-to-lot consistency study after the B-EV71 vaccine was available on the market.…”
Section: Discussionmentioning
confidence: 97%